Does Better Nutrition Raise Farm Productivity? - Strauss, John (Journal of Political Economy, 1986)
Household-level data from Sierra Leone are used to test whether higher caloric intake enhances family farm labor productivity. This is the notion behind the efficiency wages hypothesis, which has found only weak empirical support. A farm production function is estimated, accounting for the simultaneity in input and calorie choice. Instruments include prices, household demographic characteristics, and farm assets. The latter two sets of instruments are later dropped to explore the robustness of the results to different specifications of exogeneity. The exercise shows a highly significant effect of caloric intake on labor productivity, providing solid support for the nutrition-productivity hypothesis. The marginal effect on productivity falls drastically as calorie consumption rises but remains positive at moderately high levels of intake. One result is a fall in the effective price of food, a decline that is larger for households that consumer fewer calories.